2021
DOI: 10.1017/cjn.2021.332
|View full text |Cite
|
Sign up to set email alerts
|

P.051 Do clinical confounders to the neurological examination modify the diagnostic accuracy of CT-angiography for death by neurological criteria/brain death?

Abstract: Background: CT-angiography is an ancillary test used to diagnose death by neurological criteria (DNC), notably in cases of unreliable neurological examinations due to clinical confounders. We studied whether clinical confounders to the neurological examination modified CT-angiography diagnostic accuracy. Methods: Systematic review and meta-analysis of studies including deeply comatose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…121 Additionally, in a systematic review and meta-analysis of papers on the diagnostic accuracy of ancillary testing through 2022, Neves Briard et al identified 137 relevant publications and reported similar pooled sensitivities (range of 0.82–0.93) with greater heterogeneity within (σ = 0.10–0.15) than between (σ = 0.04) ancillary test types in patients who met clinical criteria for BD/DNC. 122 They noted unclear or high risk of bias, and emphasized the need for high-quality studies to evaluate ancillary tests.…”
Section: Review Of the Wbdp And Updates Since Publicationmentioning
confidence: 99%
“…121 Additionally, in a systematic review and meta-analysis of papers on the diagnostic accuracy of ancillary testing through 2022, Neves Briard et al identified 137 relevant publications and reported similar pooled sensitivities (range of 0.82–0.93) with greater heterogeneity within (σ = 0.10–0.15) than between (σ = 0.04) ancillary test types in patients who met clinical criteria for BD/DNC. 122 They noted unclear or high risk of bias, and emphasized the need for high-quality studies to evaluate ancillary tests.…”
Section: Review Of the Wbdp And Updates Since Publicationmentioning
confidence: 99%